Evolution and functional role prediction of the CYP6DE and CYP6DJ subfamilies in Dendroctonus (Curculionidae: Scolytinae) bark beetles - Quijano-Barraza, J. Manuel; Zúñiga, Gerardo; Cano-Ramírez, Claudia; López, María Fernanda; Ramírez-Salinas, Gema L.; Becerril, Moises (Frontiers in Molecular Biosciences, 2023)
Dendroctonus-bark beetles are natural components and key ecological agents of conifer forests in North and Central America, and Eurasia. They spend almost their entire lives under the bark of conifer trees, with a short dispersal phase of adult insects. They colonize hosts by means of kairomones produced by trees, which mediate interspecific communication. These compounds are present in the oleoresin, constitute a part of their defensive system and are highly toxic to these insects. Cytochromes P450 (CYP) integrate a multigene family involved in the detoxification of these compounds. Several studies have demonstrated that cytochromes of CYP6DE and CYP6DJ subfamilies hydroxylate monoterpenes, whose derivatives can act as pheromones in some Dendroctonus species. Given the diversity and functional role of CYPs in bark beetles, we investigated whether these isoforms have retained their function in the Dendroctonus genus by molecular docking, reconciliation analysis, and functional divergence tests. The results showed that the CYP6DE subfamily has undergone functional divergence, whereas the CYP6DJ subfamily has remained stable with a stronger functional constraint. The amino acid involved in functional divergence influence the conformation of the catalytic site and/or protein folding. Thus, cytochromes of the CYP6DE subfamily are apparently evolving to increase the detoxifying function of this subfamily which metabolizes mainly α-and β-pinene and produces (+) and (-)-trans-verbenol, whose negative enantiomer is used as a pheromone by several Dendroctonus species; whereas cytochromes of the CYP6DJ subfamily seem to retain their original role of hydroxylating these compounds, as these isoforms are under a strong selective pressure.